Electrophysiological findings after bilateral thoracoscopic atrial fibrillation ablation using irrigated bipolar radiofrequency energy. (25th November 2020) - Skala, T; Moravec, O; Santavy, P; Steriovsky, A; Taborsky, M
Abstract: Background: Thoracoscopic atrial fibrillation (AF) ablation (TARAFS) using irrigated bipolar radiofrequency energy should result in posterior left atrial (LA) wall isolation. Purpose: To assess the long-term durability of this "box" lesion and the extent of additional ablation needed to achieve AF non-inducibility. Methods: 22 patients with AF recurrence after bilateral TARAFS for persistent AF had a radiofrequency catheter ablation (RFA) at least three months after TARAFS. Electroanatomical voltage map was done in all patients prior to any ablation. Results: Out of 22 patients, the box lesion was not completed in 15 (68.2%). In these 15 patients, 12 had no signs of any prior ablation in endocardium (voltage >0.5mV), 2 had right pulmonary veins (PVs) isolated and 1 had left PVs isolated. At the end of RFA, box lesion was finished in all 15 patients and AF non-inducibility was achieved in 18 patients. For this endpoint, besides box lesion, mitral line and extensive coronary sinus ablation was necessary in 14, extensive CFAE ablation in 7 patients. Cavotricuspid isthmus line block was done in all patients. Conclusion: A minimally invasive thoracoscopic box-lesion ablation is considered to be a safe and effective method of stand-alone AF treatment. However, in a considerable amount of patients no signs of prior ablation are found on electroanatomical voltage map. Gaps thus cannot be found and a completely new complex ablation must be done. In a lot of patients, additional ablation is needed besides box lesion to achieve non-inducibility. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): University Hospital Olomouc